A Record of Buddhistic Kingdoms : Being an account by the Chinese monk Fa-hsien of travels in India and Ceylon (A.D. 399-414) in search of the Buddhist books of discipline - Faxian; Legge, James, 1815-1897 (Salt Lake City, UT : Project Gutenberg, 2006)
"A Record of Buddhistic Kingdoms" by Faxian is a historical account written during the early 5th century. The text recounts the travels of the Chinese monk Faxian as he journeys through India and Ceylon in search of Buddhist texts and teachings. This pilgrimage, which spans a considerable geographical landscape, provides insights into the cultural, religious, and political conditions of the regions Faxian traverses. The opening of the narrative introduces Faxian's motivation for the journey$1 (Bhis desire to locate complete copies of the Buddhist Books of Discipline. It describes his initial departures from Ch$1 (Bang-an and his encounters with various kingdoms and notable figures along the way, highlighting the challenges of travel during that era, including dangerous routes and interactions with local rulers. As Faxian and his companions make their way through desert landscapes and bustling towns filled with monks and scholars, we begin to see glimpses of the rich spiritual tapestry of Buddhism in the regions he visits. The initial chapters set the stage for a detailed exploration of Buddhism's foundations and its spread, emphasizing the deep impact of Faxian$1 (Bs journey on cultural exchanges between East and West. (This is an automatically generated summary.)s
Release date is 2006-03-28
John Bickers; Dagny and David Widger
Keywords: Buddhist pilgrims and pilgrimages -- India -- Early works to 1800; Buddhism -- Early works to 1800; Asia -- Description and travel -- Early works to 1800